Original paperEyelid xanthelasma treated with surgical excision – evaluation of long-term results - Kruk-Jeromin, Julia; Jędrzejczak, Marta; Antoszewski, Bogusław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Twenty-five women with xanthelasma located on the eyelids were treated with surgical excision. Five patients suffered from systemic diseases or had the level of serum lipids increased. Follow-up examination after 5 years revealed reoccurrence of xanthelasma in four patients. The rest of the patients had aesthetic scars and the function of eyelids was correct.